ENCOURAGING PROGRESS FOR CHILDREN WITH DIS/ABILITY: PARENT- TEACHER PARTNERSHIP - Depi Triani; Marselina, Olivtia Kesia Pebriany, Oktavia, Sari, Puput, Yola Pradita (CV. ADIBA AISHA AMIRA, 2023)
This research explores the pivotal role of collaboration between parents and teachers at GTT SLBN 1 Palangka Raya in Central Kalimantan, in supporting the development of children with dis/abilities. The primary focus is on analyzing effective collaborative strategies to create an inclusive learning environment, enabling children to optimize their potential. Through a qualitative approach, the study investigates the experiences of parents and teachers, as well as factors that facilitate or hinder successful collaboration. The anticipated outcomes aim to provide additional insights to enhance the quality of inclusive education for children with dis/abilities.